Exploring Motivational Interviewing to Engage Latinos in Advance Care Planning: A Community-Based Social Work Intervention. (August 2018) - Nedjat-Haiem, Frances R.; Carrion, Iraida V.; Gonzalez, Krystyna; Bennett, Elizabeth D.; Ell, Kathleen; O'Connell, Mary; Thompson, Beti; Mishra, Shiraz I.
Advance care planning (ACP) does not readily occur in medical settings and often gets missed. Older Latinos need ACP information to encourage advance directive (AD) completion indicating preferences for end-of-life (EOL) care. Objective: To explore the experiences with counseling using motivational interviewing (MI) techniques and social workers to encourage ACP communication among older Latinos with advance chronic diseases. This study describes stages of readiness to plan for EOL care. Design: We conducted a qualitative study with older Latinos who participated in a community-based intervention in Southern New Mexico. Methods: Participants in the intervention were selected because they received ACP education plus counseling involving MI to address resistance to ACP. Motivational interviewing counseling involved the following: (1) engaging in structured dialogue about ACP, (2) using and completing AD documentation, (3) encouraging ACP communication with providers and families, and (4) applying AD information into actionable behavior. We utilized a constant comparative method and thematic analysis to explore the meaning of older Latinos' experiences with MI counseling and stages of change. Results: Participants (n = 32) were mostly women (74.3%), half born in the United States and half from Mexico in the United States on average for 31.75 (standard deviation 16.22) years. Many had less than sixth grade education (31.3%) or had not completed high school (21.9%). Key themes indicate the following stages of change: (1) precontemplation, (2) contemplation, (3) preparation, (4) ACP action, and (5) maintenance. Conclusion: This study contributes to the literature by identifying areas for adaption to enhance understanding and increase information to ultimately achieve the completion of ACP among Latinos.